Insight to Edifice of Moving Message Boards - Madandola Tajudeen Niyi; Sakariyay Sherif Niyi; Oyelowo Philip Olalekan (Budapest International Research and Critics University, 2022)
The most significant means of communicating from a computer to an individual is moving message boards also called Text Electronic Display. It is an element of a sign that is capable of displaying words, symbols, figures, or images that electronically or mechanically change by remote or automatic means. It is based on light-emitting diodes and it is connected in an array flat form. It is useful for creating attention-getting messages presentations, advertisements and location identifiers. The 1024 counter enables the information to be displayed sequentially as desire. The driver unit uses transistor to amplify the signal strength of the counter output. The output unit enables the information to be displayed using light emitting diodes (LEDs). Micro-controller AT89C51 provides output to control the logic levels for the sixteen rows of 32 by 16 matrix edifice.